To solve the algebraic expression -4(y - 7), we'll follow the order of operations (PEMDAS).
1. First, distribute -4 to terms inside the parentheses:
-4 * y = -4y
-4 * 7 = -28
2. Rewrite the expression with the distributed terms:
-4(y - 7) = -4y + 28
Therefore, the simplified algebraic expression is -4y + 28.
-4(y - 7)
solve the algebraic expression
3 answers
1/4x - 36
which expression is equivalent.
1/4 (x + 144)
1/4(x - 144)
1/4 (x - 9)
4x - 9
which expression is equivalent.
1/4 (x + 144)
1/4(x - 144)
1/4 (x - 9)
4x - 9
The expression equivalent to 1/4x - 36 is 1/4(x + 144).
To see why, let's simplify each option:
1/4(x + 144) = (1/4)x + (1/4)(144) = 1/4x + 36
1/4(x - 144) = (1/4)x - (1/4)(144) = 1/4x - 36
1/4(x - 9) = (1/4)x - (1/4)(9) = 1/4x - 9/4
4x - 9 is not equivalent to 1/4x - 36.
Therefore, the only option equivalent to 1/4x - 36 is 1/4(x + 144).
To see why, let's simplify each option:
1/4(x + 144) = (1/4)x + (1/4)(144) = 1/4x + 36
1/4(x - 144) = (1/4)x - (1/4)(144) = 1/4x - 36
1/4(x - 9) = (1/4)x - (1/4)(9) = 1/4x - 9/4
4x - 9 is not equivalent to 1/4x - 36.
Therefore, the only option equivalent to 1/4x - 36 is 1/4(x + 144).